Artesunate restores mitochondrial fusion‐fission dynamics and alleviates neuronal injury in Alzheimer's disease models - Qin, Yi‐Ren; Ma, Chi‐Qian; Jiang, Jian‐Hua; Wang, Da‐Peng; Zhang, Quan‐Quan; Liu, Mei‐Rong; Zhao, Hong‐Ru; Fang, Qi; Liu, Yang (Journal of neurochemistry, 2022)
Alzheimer's disease (AD) remains a leading cause of dementia and no therapy that reverses underlying neurodegeneration is available. Recent studies suggest the protective role of artemisinin, an antimalarial drug, in neurological disorders. In this study, we investigated the therapeutic potential of artesunate, a water‐soluble derivative of artemisinin, on amyloid‐beta (Aβ)‐treated challenged microglial BV‐2, neuronal N2a cells, and the amyloid precursor protein/presenilin (APP/PS1) mice model. We found that Aβ significantly induced multiple AD‐related phenotypes, including increased expression/production of pro‐inflammatory cytokines from microglial cells, enhanced cellular and mitochondrial production of reactive oxygen species, promoted mitochondrial fission, inhibited mitochondrial fusion, suppressed mitophagy or biogenesis in both cell types, stimulated apoptosis of neuronal cells, and microglia‐induced killing of neurons. All these in vitro phenotypes were attenuated by artesunate. In addition, the over‐expression of the mitochondrial fission protein Drp‐1, or down‐regulation of the mitochondrial fusion protein OPA‐1 both reduced the therapeutic benefits of artesunate. Artesunate also alleviated AD phenotypes in APP/PS1 mice, reducing Aβ deposition, and reversing deficits in memory and learning. Artesunate protects neuronal and microglial cells from AD pathology, both in vitro and in vivo. Maintaining mitochondrial dynamics and simultaneously targeting multiple AD pathogenic mechanisms are associated with the protective effects of artesunate. Consequently, artesunate may become a promising therapeutic for AD. Artesunate, a derivative of antimalaria artemisinin, alleviates amyloid‐beta (Aβ)‐induced Alzheimer's disease (AD). The benefits of artesunate involve the activation of mitochondrial biogenesis, the shift of mitochondrial dynamics from fission toward fusion, and the enhanced mitophagy in microglial cells and neurons. Up‐regulating mitochondrial fission protein dynamin‐related/−like protein 1 (Drp1) or knocking down mitochondrial fusion protein optic atrophy 1 (OPA‐1) partially and significantly dampens the protective effects of artesunate. Artesunate may become a promising therapy for AD.